Day Centers as Meeting Places and Turning Points in the Rehabilitation Pathway. Issue 1 (2nd January 2016) - Peloso, Paolo Francesco; Valentini, Lucia
Abstract: In this article we describe the features of the Day Centers in the Italian Mental Health Departments. The Day Centers is a place, generally separate from the Community Mental Health Centers, where psychiatric services offer recreation and rehabilitation activities to a number of clients, ranging from 5–10 to 100 or more, depending on the size of the facility and the type of activity undertaken, for a period that should be limited and finalized to the full reintroduction within society and a work environment. We describe multiple models and functions of the Italian Day Centers in an historical perspective.